The Implementation of the Mindful-hand Strategy in Acquiring Islamic Concepts among Fifth Graders Female Students - Mohammed, Qutaiba Hameed; Al-Sabawi, Mohammed Abdullah (Journal of Tikrit University for Humanities, 2024)
The aim of the current research is to identify the impact of the Think-Pair-Share strategy on acquiring Islamic concepts among female fifth graders. The researchers utilized a random experimental design with a two-dimensional test and partial adjustment for two equivalent groups (experimental and control). The research sample consisted of 47 female students from Al-Hikmah Primary School for Girls, affiliated with the Directorate of Education in Nineveh. The students were randomly distributed between two groups, one experimental consisting of 24 students (taught using the Think-Pair-Share strategy) and the other control consisting of 23 students (taught using the traditional method). The groups were matched in terms of chronological age, the previous year’s average in Islamic education, intelligence, and the parents’ educational level. The experiment was implemented in the first semester of the academic year 2023-2024. The researchers developed a test for Islamic concepts as a research tool. They used several statistical methods, including the independent samples t-test. Based on the results of the current research, the researchers drew several conclusions, provided recommendations, and suggested proposals related to their research topic.